STANDARDIZATION OF SPECIFIC AND NON-SPECIFIC PARAMETERS OF DAYAK ONION BULB (ELEUTHERINE PALMIFOLIA L. MERR.) - Wiwit Zuriati Uno; Nazwa Salfadila Hasan; Serlin N. Tilola; Salwa Rumampuk; Mohammad Qarlan Pratama; Meira Kumala Arista (JIMR : Journal Of International Multidisciplinary Research, 2025)
This study aimed to determine the specific and non-specific parameters of Dayak onion bulb extract as a basis for herbal standardization. The research methods included organoleptic identification, phytochemical screening, Thin Layer Chromatography (TLC) analysis, and determination of non-specific parameters, namely moisture content, total ash content, Total Plate Count (TPC), and Yeast and Mold Count (YMC). Phytochemical screening showed the presence of alkaloids, flavonoids, tannins, and saponins, while steroids and terpenoids were not detected. The TLC profile showed several spots with varying Rf values, indicating the presence of compounds with different polarity levels. The moisture content (5.07%) and total ash content (4.31%) met the standards of the Indonesian Herbal Pharmacopoeia. TPC (5.4 × 10² CFU/mL) and YMC (3.2 × 10² CFU/mL) were below the permissible limits. These results indicate that Dayak onion bulb extract meets the required specific and non-specific parameters and is suitable for use as a standardized herbal raw material.